TURUNAN FLAVONOID DARI NICOLAIA SPECIOSA HORAN - Mulianingsih, Lia
Plant is one of the most important. natural resources for man-kind. Therefore, chemicals of plant origin have been the subject of investigation by the chemists. How-ever, the chemical aspect of a number of plants, which have been shower to have certain physiological activity, have not been thoroughly investigated. Those plants include many species of the family Zingiberaceae which are easily found in Indonesia. The present investigation concerns with the chemical constituents of the rhizome of Nicolaia speciosa Horan (Fain. Zingiberaceae) particularly the chemical derivatives of flavonoid. Preliminary examination of the methanol extract of the rhizome using, the standard methods for the flavonoid derivatives showed the presence of flavonoids. Following this observation, the methanol extract was partitioned with petroleum ether and ethyl acetate, successively. The petroleum ether fraction showed the presence of hydroxyl, aldehyde, and aromatic functions on chemical and infrared spectroscopic examinations, and gave a red co-loured 2,4- dinitrophenylhydrazone derivative, m.p. 193-194 Â°C. This fraction and the hydrazone derivative had not be-en further examined. The ethyl acetate fraction, which gave positive tests for flavonoid derivatives, consisted of at least right components on two dimensional thin-layer and paper chromatographics examinations. Upon acid hydrolysis, the ethyl acetate fraction gave different chromatograms as that of the original ex-tract. It was also found that the product of hydrolysis was a mixture of at least seven components. The mixture on column chromatography gave among others a needle-like crystalline compound. Based on ultra-violet spectroscophic examinations, the solid compound was found to be 5-hydroxy-flavone or its derivatives.